Human pancreatic beta-like cells converted from fibroblasts - Saiyong Zhu (Nature Portfolio, 2016)
Insulin-producing pancreatic beta cells, generatedin vitro, could lead to new anti-diabetic therapies. Here, Zhu et al. convert human fibroblasts into endodermal progenitors that differentiate in vitrointo glucose-responsive beta-like cells that, following transplantation in mice, protect from diabetes.